THE SUCCESS OF CENTRAL JAVA EXPORT MSMEs THROUGH EFFECTIVENESS OF SEMARANG FTA CENTER CONSULTATION - Turidobroto, Bastian; Indriani, Farida (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2023)
This research is aimed at testing the effectiveness of the Semarang FTA center consultation on the success of Central Java MSME exports. The problem in this research is the low effectiveness of the Semarang FTA Center program in providing assistance regarding the success of MSMEs in Central Java in carrying out export activities, this is shown by the small number of MSMEs that have successfully exported, namely 35 MSMEs out of 589 MSMEs that have received consultation. In this research, the research object is related to the problems to be studied, namely the effectiveness of the Semarang FTA center consultation on the success of Central Java MSME exports. The MSMEs studied are MSMEs in Central Java that already carry out exports. These empirical findings indicate that the consultation that MSMEs expect is more about financing and sales communication with external parties. The obstacles experienced by the Semarang FTA Center in the Central Java MSME policy to successfully export are: The lack of knowledge of MSMEs regarding legalities such as taxpayer identification numbers (NPWP) and several regulations, b. difficult access to obtain financing from banks and financial institutions. c. lack of assistance for MSMEs in improving quality, product competitiveness, governance and company management. d. Production area problems, including the lack of product standards, are an obstacle for MSMEs to penetrate the global market. e. marketing problems. MSMEs have limited information regarding market opportunities, minimal promotion, and limited digital and financial literacy.